Visitors' satisfaction towards quality environment, services and facilities provided in Kilim Karst Geoforest Park, Langkawi, Malaysia - Safari, Mohamad Safee (2014)
Kilim Karst Geoforest Park (KKGP) is one of the three Geoparks located in the Langkawi Island that offers nature-based attraction to visitors. Since it was announced as Malaysia’s (and Southeast Asia’s) first Global Geopark in June 2007 by the United Nations Educational Scientific and Cultural Organization (UNESCO), many of services and facilities development have been implemented to the convenience of visitors at the park. However, several issues have risen from the implementation of development projects in the park for instance, the decline in the quality of the environment, inadequate services and facilities,congestion and interference to local communities due to increases in the number of visitors to the park. Thus, the main objective of this study is to measure the level of visitors’ satisfaction towards quality of the environment, services and facilities at KKGP and to determine the attributes that need priority for improvement. Besides, it is also to determine the socio-demographic and visit characteristics of visitors that influence the level of satisfaction. The gap analysis is used to measure the level of satisfaction by calculating the perceived performance minus the expectation. Visitors would be unsatisfied if the values of expectation are greater than values of perceived performance and vice versa. Visitors’ expectation and perceived performance are measured using the 5-point Likert scale ranging from (1) “very unsatisfied” to (5) “very satisfied”. This study uses the eco-tourist service quality (ECOSERV) dimension that has been adapted from service quality (SERVQUAL) dimension to assess the quality of environment, services, and facilities provided at the ecotourism site. Also, the study uses the grid of expectation-performance analysis (EPA) that has been adapted from importance performance analysis (IPA) to identify the attributes that need priority improvement. 400 samples of visitors visiting the park were conveniently selected to respond to the self-administered questionnaire over a two-week period in March 2013. The results of the study have found that the level of visitors’ satisfaction towards the qualities of environment, services and facilities in the park is low. The analysis of the GAP has found that of the 27 attributes, 17 items indicate that visitors are less satisfied of which 6 items need for urgent improvement. In addition, the analysis of the factors influencing the satisfaction levels indicates that female visitors are more dissatisfied than male visitors. Another factor of the effects is the nationality of the visitors in which foreign visitors are more dissatisfied compared to Malaysians. Other socio-demographic and visit characteristics of visitors that influence the levels of satisfaction are, occupation,level of education, travel companions, visit frequency, number of hours at the park and usage of tour package. The findings of the study will be useful for the park management especially for Langkawi Development Authority (LADA) to focus on the product attribute and to determine features that are important and need to be maintained and to be prioritized for improvement. The study also will be help LADA to manage and improve on their weaknesses as stated by visitors, so they could take remedial actions to served the visitors better.